Food insecurity and self-rated health in rural Nicaraguan women of reproductive age: a cross-sectional study - Pérez, Wilton (Int J Equity Health, 2018)
BACKGROUND: Access to food is a basic necessity, and food insecurity may impair the individual’s well-being and health. Self-rated health measurements have frequently been used to assess population health. Little is known, however, as to whether food security is associated with self-rated health in low- and middle-income settings. This study aims at analyzing the association between food security and self-rated health among non-pregnant women of reproductive age in a rural Nicaraguan setting. METHODS: Data was taken from the 2014 update of a health and demographic surveillance system in the municipalities of Los Cuatro Santos in northwestern Nicaragua. Fieldworkers interviewed women about their self-rated health using a 5-point Likert scale. Food insecurity was assessed by the household food insecurity access (HFIAS) scale. A multilevel Poisson random-intercept model was used to calculate the prevalence ratio. RESULTS: The survey included 5866 women. In total, 89% were food insecure, and 48% had poor self-rated health. Food insecurity was associated with poor self-rated health, and remained so after adjustment for potential confounders and accounting for community dependency. CONCLUSION: In this Nicaraguan resource-limited setting, there was an association between food insecurity and poor self-rated health. Food insecurity is a facet of poverty and measures an important missing capability directly related to health.